Cognitive decline associated with anticholinergics, benzodiazepines and Z‐drugs: Findings from The Irish Longitudinal Study on Ageing (TILDA). Issue 7 (18th December 2020) - Moriarty, Frank; Savva, George M.; Grossi, Carlota M.; Bennett, Kathleen; Fox, Chris; Maidment, Ian; Loke, Yoon K.; Steel, Nicholas; Kenny, Rose Anne; Richardson, Kathryn
Abstract : Aims: To estimate the association between patterns of anticholinergic, benzodiazepine and Z‐drug medication use and change in cognitive function in middle‐aged and older adults. Methods: This prospective cohort study used data from the first three waves of The Irish Longitudinal Study on Ageing (TILDA), including community‐dwelling adults aged ≥50 years followed for up to 4 years ( n = 7027). Cognitive function was assessed using the Mini Mental State Examination, animal naming test and word recall tests. Regular medication use was self‐reported at baseline and follow‐up interviews at 2 and 4 years. Pharmacy dispensing claims for a subset ( n = 2905) allowed assessment of medication use between interviews and cumulative dosage. Medication use at consecutive waves of TILDA was analysed in relation to change in cognitive function between waves. Results: Strongly anticholinergic medications (Anticholinergic Cognitive Burden scale 3), benzodiazepines and Z‐drugs were reported by 7.3%, 5.8% and 5.1% of participants, respectively, at any time during the study. Adjusting for potential confounders, new anticholinergic use between interviews was associated with change in recall score (−1.09, 95% confidence interval −1.64, −0.53) over 2 years compared to non‐use, but not with MMSE (0.07; 95% CI −0.21, 0.34) or animal naming (−0.70; 95% CI −1.43, 0.03). The pharmacy claims analysis was consistent with this finding. Other hypothesised associations were not supported. Conclusions: Except for new use of anticholinergic medications, no other findings supported a risk of cognitive decline over 2‐year periods in this middle‐aged and older cohort. Patients and prescribers should weigh this potential risk against potential benefits of commencing anticholinergic medications.